Pengolahan Ikan Bandeng Menjadi Snack Kekinian Untuk Meningkatkan Perekonomian Masyarakat Desa Aramiyah - Naz, Aisyah; Mutia, Nur Balqis; Inani, Zahra; Ikshan, Khairul; Iqbal Aldiansyah, Muhammad; Maghfirah, Umi; Nabila, Atika; Mutia, Siti (MEUSEURAYA - Jurnal Pengabdian Masyarakat, 2023)
Aramiyah is one of the villages in East Aceh with the majority of people working in oil palm plantations, making bricks and cultivating fish ponds. The current problem is that the selling price of palm oil and bricks is decreasing so that people are experiencing an economic downturn. An alternative solution that can be implemented is by optimizing the processing of one of the results of community ponds. Milkfish is one of the potentials that exist in Aramiyah village, Birem Bayeun district, which is only used as a side dish to accompany rice. The potential of milkfish can be optimized by making it into marketable processed products such as meatballs. The aim of this service is to increase the knowledge and skills of the community by exploiting regional potential that exists but has not been utilized optimally, namely creating milkfish into contemporary snacks. The activity methods carried out include preparation, counseling and demonstration. The results achieved were that the community, especially housewives in Aramiyah village, gained new experience in using the results of milkfish ponds to make homemade meatballs to improve family nutrition that were cheap, easy and suitable for sale.